Assessing context suitability (generalizability, external validity, applicability or transferability) of findings in evidence syntheses in healthcare—An integrative review of methodological guidance. (29th September 2020) - Weise, Alina; Büchter, Roland; Pieper, Dawid; Mathes, Tim
Abstract : Background: Evidence syntheses provide the basis for evidence‐based decision making in healthcare. To judge the certainty of findings for the specific decision context evidence syntheses should consider context suitability (ie, generalizability, external validity, applicability or transferability). Our objective was to determine the status quo and to provide a comprehensive overview of existing methodological recommendations of Health Technology Assessment (HTA) and Systematic Review (SR) producing organizations in assessing context suitability of evidence on effectiveness of health care interventions. Additionally, we analyzed similarities and differences between the recommendations. Methods: In this Integrative Review we performed a structured search for methods documents from evidence synthesis producing organizations that include recommendations on appraising context suitability in effectiveness assessments. Two reviewers independently selected documents according to predefined eligibility criteria. Data were extracted in standardized and piloted tables by one reviewer and verified by a second reviewer. We performed a thematic analysis to identify and summarize the main themes and categories regarding recommended context suitability assessments. Results: We included 14 methods documents of 12 organizations in our synthesis. Assessment approaches are very heterogeneous both regarding the general concepts (eg, integration in the evidence synthesis preparation process) and the content of assessments (eg, assessment criteria). Conclusion: Some heterogeneity seems to be justified because of the need to tailor the assessment to different settings and medical areas. However, most differences were inexplicable. More harmonization is desirable and appears possible.